India and the Indo-Pacific in the post-pandemic world order - Vinodan, C.; Alexander, J.K. (Penerbit UKM, 2024)
Indo-Pacific is a geopolitical construct that combines the Indian Ocean and the Pacific Ocean, representing the new strategic reality of the twenty-first century. Indo-Pacific is also considered significant for countries as it is a strategic and economic domain with a critical role in maritime security and cooperation. With a strategic location in the Indo-Pacific region, India is now a theatre of opportunity to increase its role regionally and globally. The Indian Ocean carries 90 per cent of India’s trade and its energy sources, and nearly 50 per cent of India’s trade is centred in the Indo-Pacific region. India’s relations with incredible powers, island nations, and smaller littoral states will significantly shape India’s Indo-Pacific strategy. Increasing non-traditional threats and growing challenges from rising China are significant drivers of India’s policy options in the post-pandemic world. India’s soft power diplomacy and bilateral and multilateral partnerships in the region continue to be decisive factors for security and balance of power in the post-pandemic scenario. Thus, the geo-strategic environment of the Indo-Pacific in the post-pandemic era is crucial for India and the countries in the Indo-Pacific region as a whole for their growth, development, and security. Thus, this paper explores India’s crucial role in ensuring the security and equilibrium of the post-pandemic Indo-Pacific through a comprehensive analysis of its strategic initiatives and regional dynamics.